Math, asked by Harpreetkaur11, 1 year ago

the roots of the question x^2-3x-m(m+3)=0where m is constant

Answers

Answered by mysticd
1
Hi ,
x² - 3x - m( m + 3 ) = 0

Splitting the middle term ,

x² + mx - ( m + 3 ) x - m( m + 3 ) = 0

x ( x + m ) - ( m + 3 ) [ x + m ] = 0

( x + m ) [ x - ( m + 3 ) ] = 0

x + m = 0 or x - ( m + 3 ) = 0

x = - m or x = ( m + 3 )

I hope this helps you.

:)

Harpreetkaur11: thankyou so much
Answered by priya476
0
The roots of the above equation are -m and m+3
Similar questions